Detecção das mudanças costeiras na margem leste do estuário do Rio Pará: uma análise multitemporal (1987-2019) utilizando sensoriamento remoto. - GUIMARÃES, Diandra Karina Martins (Universidade Federal do Pará, 2024)
In the Coastal and Estuarine Zone of Pará (ZCEP) occurs a complex dynamics influenced by meteorological forces (rainfall, winds, extreme events), fluvial (flow) and marine (tides, currents, waves). The forcings affect the coastline (CL) of the estuaries margins causing changes that depend on the degree of exposure of the area and the intensity of the forcings. Therefore, the detection of the places that happen the processes of erosion and/or accretion of the coastline becomes interesting to observe the changes in the surroundings of the islands and municipalities of the eastern margin of the Pará River Estuary. The work area is located on the eastern margin of the Pará river estuary, in the section: Mosqueiro island, Santo Antônio do Tauá, Colares island (edge of the middle estuary), Vigia and São Caetano de Odivelas (edge of the lower estuary). To achieve the results, LANDSAT satellite images were acquired (1987; 1993; 1999; 2004; 2008; 2013 and 2019) and the Digital Shoreline Analysis System (DSAS) was used to more accurately identify and calculate the rates of variation of changes in erosion and accretion areas in the LC. NSM, LRR and EPR parameters were applied on the east margin of the Pará river estuary (117 km) in the 32-year period of analysis, with a total of 1130 transects generated. In the middle estuary, the tendency to erosion was higher, predominating in Mosqueiro Island with an average erosion rate of -38m and an average accretion rate of 22.97m, related to the average rates of variation of -0.58m/year (EPR) and -0.54m/year (LRR) and in Santo Antônio do Tauá with LRR and EPR parameters identifying average rates of change of -1.67m/year (LRR) and -1.55m/year (EPR). Only on the Colares island there was a tendency to accretion, with an average erosion rate of -96.29m and an average accretion rate of 116.49m, where the maximum accretion and erosion rates are 405.61m and -396.87m, respectively. While in the lower estuary there was a greater tendency to accretion, where in Vigia there was an average rate of change of 1.26 m/year and a maximum rate of accretion of 10.06 m/year in the EPR, and an average rate of change of 0.64 m/year and maximum accretion rate of 7.22 in the LRR. In São Caetano de Odivelas, the average rate of change in the EPR parameter was 0.40 m/year and in the LRR parameter it was 0.25 m/year and in the NSM it was 13.09 m. Comparing the margins of the Estuary, the east margin is under the influence of a low hydrodynamics, while the west margin is under a high hydrodynamics where erosion predominates, demonstrating that in the same estuary the processes occur in a different way, where the areas of high erosion are related to the morphology of the site and location of the area being more exposed to forcing.